Analysis of carbohydrate, protein and fat levels using various type rice with different cooking process. Issue 1 (1st June 2022) - Cintya, H; Putra, E D L; Muhammad, M; Pranata, C; Syahputra, H D
Abstract: The highest comsumption white rice can increase risk of diabetes deseases. The aimed of this study was to determine nutrient as carbohydrate, ptotein, and fat levels with various types of rice with different cooking process. All of type rice conducted with different cooking process using steamed and rice cooker. Analysis of carbohydrates using UV-Vis spectrophotometry, analysis of fats using the soxhletation method and protein levels using Kjeldhal method. The result of this study that the highest carbohydrate levels is found in raw white rice at 126.124 mg/kg, while after cooking process that the highest carbohydrate levels was found in white rice used ricecooker at 103.400 mg/kg. The highest protein levels before processed was found in raw black rice at 11.16%, while the lowest was found in white rice at 8.71%, after cooking processed the highest protein levels found in black rice cooker at 5.12 %, while the lowest was found in steamed black rice at 3.89%. The highest fat levels before processed was found in black rice of 0.214%, while after cooking processed, the highest fat levels was found in steamed white rice at 0.076%. The conclusion of this study that there are the effects of cooking processed on nutrient.